Hybrid Solar-LPG Dryer for Efficient Shallot Post-Harvest Drying - Mustajib, Mohamad Imron; Hasan, Fuad; Wahyuningrum, Rima Tri; Ibrohim, Ikrom Maulana Malik; Yudiansyah, Hilman Tsaqif; Islam, Moh Idzul; Prasetyo, Reynaldi; Albarizy, Ferdy (Indonesian Journal of Cultural and Community Development, 2025)
Background: Shallots are an important crop in Indonesia, but post-harvest drying remains inefficient, especially in Karang Penang Oloh Village, where traditional sun drying leads to quality loss and long drying times. Aims: This study aims to design a hybrid solar-LPG pyramid dryer to improve drying efficiency and product quality for local farmers. Results: The dryer successfully dried 20 kg of shallots in 10 hours, reducing moisture content from 86% to 12.44%-15.99%. Novelty: The hybrid solar-LPG system offers a scalable and efficient solution for larger-scale drying. Implications: This technology can enhance post-harvest processing, improving both drying time and product quality, with potential for broader agricultural applications. Highlights: Hybrid solar-LPG system reduces drying time for shallots. Moisture content of shallots reduced to optimal levels (12.44%-15.99%). Pyramid dryer design improves drying efficiency and product quality. Keywords: Shallots, Post-Harvest, Drying, Hybrid Technology, Pyramid Dryer